Aryl substitution of pentacenes - Waterloo, Andreas R.; Sale, Anna-Chiara; Lehnherr, Dan; Hampel, Frank; Tykwinski, Rik R. (Beilstein Journal of Organic Chemistry, 2014)
A series of 11 new pentacene derivatives has been synthesized, with unsymmetrical substitution based on a trialkylsilylethynyl group at the 6-position and various aryl groups appended to the 13-position. The electronic and physical properties of the new pentacene chromophores have been analyzed by UV–vis spectroscopy (solution and thin films), thermoanalytical methods (DSC and TGA), cyclic voltammetry, as well as X-ray crystallography (for 8 derivatives). X-ray crystallography has been specifically used to study the influence of unsymmetrical substitution on the solid-state packing of the pentacene derivatives. The obtained results add to our ability to better predict substitution patterns that might be helpful for designing new semiconductors for use in solid-state devices.
Keywords: carbon-nanomaterials; organic semiconductor; pentacene; π-stacking; polycyclic aromatic hydrocarbon; solid-state structure

(untitled) - Figueira-Duarte, T. M.; Müllen, K. (Chem. Rev., 2011)

(untitled) - Hains, A. W.; Liang, Z.; Woodhouse, M. A.; Gregg, B. A. (Chem. Rev., 2010)

(untitled) - Lucas, B.; Trigaud, T.; Videlot-Ackermann, C. (Polym. Int., 2012)

(untitled) - Beaujuge, P. M.; Fréchet, J. M. J. (J. Am. Chem. Soc., 2011)

(untitled) - Cheng, Y.-J.; Yang, S.-H.; Hsu, C.-S. (Chem. Rev., 2009)

(untitled) - Mártin, N.; Sánchez, L.; Herranz, M. Á.; Illescas, B.; Guldi, D. M. (Acc. Chem. Res., 2007)

(untitled) - Dang, M. T.; Hirsch, L.; Wantz, G.; Wuest, J. D. (Chem. Rev., 2013)

(untitled) - Arias, A. C.; MacKenzie, J. D.; McCulloch, I.; Rivnay, J.; Salleo, A. (Chem. Rev., 2010)

(untitled) - Hains, A. W.; Liang, Z.; Woodhouse, M. A.; Gregg, B. A. (Chem. Rev., 2010)

(untitled) - Mei, J.; Diao, Y.; Appleton, A. L.; Fang, L.; Bao, Z. (J. Am. Chem. Soc., 2013)

(untitled) - Lehnherr, D.; Tykwinski, R. R. (Materials, 2010)

(untitled) - Lehnherr, D.; Tykwinski, R. R. (Aust. J. Chem., 2011)

(untitled) - Anthony, J. E. (Chem. Rev., 2006)

(untitled) - Anthony, J. E. (Angew. Chem., Int. Ed., 2008)

(untitled) - Bendikov, M.; Wudl, F.; Perepichka, D. F. (Chem. Rev., 2004)

(untitled) - Anthony, J. E.; Brooks, J. S.; Eaton, D. L.; Parkin, S. R. (J. Am. Chem. Soc., 2001)

(untitled) - Lehnherr, D.; Murray, A. H.; McDonald, R.; Tykwinski, R. R. (Angew. Chem., Int. Ed., 2010)

(untitled) - Lehnherr, D.; Murray, A. H.; McDonald, R.; Ferguson, M. J.; Tykwinski, R. R. (Chem.–Eur. J., 2009)

(untitled) - Lehnherr, D.; Gao, J.; Hegmann, F. A.; Tykwinski, R. R. (J. Org. Chem., 2009)

(untitled) - Lehnherr, D.; McDonald, R.; Ferguson, M. J.; Tykwinski, R. R. (Tetrahedron, 2008)

(untitled) - Lehnherr, D.; Gao, J.; Hegmann, F. A.; Tykwinski, R. R. (Org. Lett., 2008)

(untitled) - Lehnherr, D.; Tykwinski, R. R. (Org. Lett., 2007)

(untitled) - Kuninobu, Y.; Seiki, T.; Kanamaru, S.; Nishina, Y.; Takai, K. (Org. Lett., 2010)

(untitled) - Li, Y.; Wu, Y.; Liu, P.; Prostran, Z.; Gardner, S.; Ong, B. S. (Chem. Mater., 2007)

(untitled) - Lee, S. H.; Kim, S. H.; Choo, D. J.; Jang, J. (Org. Electron., 2010)

(untitled) - Wang, C.; Dong, H.; Hu, W.; Liu, Y.; Zhu, D. (Chem. Rev., 2012)

(untitled) - Zade, S. S.; Bendikov, M. (J. Phys. Org. Chem., 2012)

(untitled) - Biermann, D.; Schmidt, W. (J. Am. Chem. Soc., 1980)

(untitled) - Bénard, C. P.; Geng, Z.; Heuft, M. A.; VanCrey, K.; Fallis, A. G. (J. Org. Chem., 2007)

(untitled) - Anthony, J. E.; Eaton, D. L.; Parkin, S. R. (Org. Lett., 2002)

(untitled) - Etschel, S. H.; Waterloo, A. R.; Margraf, J. T.; Amin, A. Y.; Hampel, F.; Jäger, C. M.; Clark, T.; Halik, M.; Tykwinski, R. R. (Chem. Commun., 2013)

(untitled) - Zhang, J.; Pawle, R. H.; Haas, T. E.; Thomas, S. W., III (Chem.–Eur. J., 2014)

(untitled) - Kim, Y.-E.; Park, J.-W. (Mol. Cryst. Liq. Cryst., 2006)

(untitled) - Zhang, X.; Jiang, X.; Luo, J.; Chi, C.; Chen, H.; Wu, J. (Chem.–Eur. J., 2010)

(untitled) - Lehnherr, D.; McDonald, R.; Tykwinski, R. R. (Org. Lett., 2008)

(untitled) - Waterloo, A. R.; Kunakom, S.; Hampel, F.; Tykwinski, R. R. (Macromol. Chem. Phys., 2012)

(untitled) - Boudebous, A.; Constable, E. C.; Housecroft, C. E.; Neuburger, M.; Schaffner, S. (Acta Crystallogr., Sect. C, 2006)

(untitled) - Vets, N.; Smet, M.; Dehaen, W. (Synlett, 2005)

(untitled) - Maulding, D. R.; Roberts, B. G. (J. Org. Chem., 1969)

(untitled) - Platt, A. D.; Day, J.; Subramanian, S.; Anthony, J. E.; Ostroverkhova, O. (J. Phys. Chem. C, 2009)

(untitled) - Ostroverkhova, O.; Shcherbyna, S.; Cooke, D. G.; Egerton, R. F.; Hegmann, F. A.; Tykwinski, R. R.; Parkin, S. R.; Anthony, J. E. (J. Appl. Phys., 2005)

(untitled) - Lee, K. O.; Gan, T. T. (Chem. Phys. Lett., 1977)

(untitled) - Mattheus, C. C.; Dros, A. B.; Baas, J.; Oostergetel, G. T.; Meetsma, A.; de Boer, J. L.; Palstra, T. T. M. (Synth. Met., 2003)

(untitled) - Mattheus, C. C.; Dros, A. B.; Baas, J.; Meetsma, A.; de Boer, J. L.; Palstra, T. T. M. (Acta Crystallogr., Sect. C, 2001)

(untitled) - Siegrist, T.; Kloc, C.; Schön, J. H.; Batlogg, B.; Haddon, R. C.; Berg, S.; Thomas, G. A. (Angew. Chem., Int. Ed., 2001)

(untitled) - Mattheus, C. C.; de Wijs, G. A.; de Groot, R. A.; Palstra, T. T. M. (J. Am. Chem. Soc., 2003)

(untitled) - Campbell, R. B.; Robertson, J. M.; Trotter, J. (Acta Crystallogr., 1962)

(untitled) - Anthony, J. E.; Subramanian, S.; Parkin, S. R.; Park, S. K.; Jackson, T. N. (J. Mater. Chem., 2009)

(untitled) - Kim, D. H.; Lee, D. Y.; Lee, H. S.; Lee, W. H.; Kim, Y. H.; Han, J. I.; Cho, K. (Adv. Mater., 2007)

(untitled) - Lim, Y.-F.; Shu, Y.; Parkin, S. R.; Anthony, J. E.; Malliaras, G. G. (J. Mater. Chem., 2009)